A MULTIDIMENSIONAL ANALYSIS OF PHYSIOLOGICAL AND MECHANICAL VARIABLES AMONG ARCHERS OF DIFFERENT LEVELS OF EXPERTISE - Mohamad Razali, Abdullah; Norzulaika, Alias; Vijayamurugan, Eswaramoorthi (2018)
The present study investigates the various physiological and mechanical techniques employed by archers of varying skill levels. A total number of four archers two females (gold medalist and non-medalist) and two males (expert and novice) participated in the study in two separate experiments. A sum of four shimmer sensors were used to examine, compare and differentiate the postural balance, movement of the bow, muscular activations of the muscle flexor digitorum superficial and muscle extensor digitorum as well as the heart rate variability of the archers. The results revealed that elite and medalist archers are better in controlling their postural sway, reducing the extensors. Both medalist and movement of their bows, have greater activation of muscle elite archers maintained a lower heart rate, hence achieved consistency and maximum scores as opposed to the non-medalist and novice archers.